Experimental Verification of Harmonic Load Models - Balci, M. E.; Ozturk, D.; Karacasu, O.; Hocaoglu, M. H. (IEEE, 2008)
Present day power systems invariably have nonlinear loads, which inject harmonies into the system and give rise to nonsinusoidal voltages and currents. Power quality issues are a prime concern of the power industries as well as of customers. Thus under these conditions, it becomes imperative to study these nonlinear loads; their characteristics and effects. Accordingly, the harmonic analyses have become a regularly used tool in predicting the effects of harmonic producing loads on power systems. State of power system can be obtained in respect to the results of these analyses. The accuracy of these results depends on the modeling of harmonic producing loads. There are a large number of harmonic analysis methods that are in widespread use. In these analyses, the harmonic producing loads are widely modeled by various techniques namely; Constant Current Sources, Norton and Crossed Frequency Admittance Matrix. In this paper, the sensitivities of these models are evaluated for the system, which covers some of the harmonic producing loads, under the various waveform cases of supply voltages.
43rd International-Universities-Power-Engineering Conference -- SEP 01-04, 2008 -- Padova, ITALY
Keywords: Harmonics; Harmonic analyses; Load modeling; Constant Current Source model; Norton model; Crossed Frequency Admittance Matrix model